Analisis Pengaruh Promosi, Kepercayaan Dan Kualitas Layanan Terhadap Keputuan Pembelian Online Pada Mahasiswa Asal Banyuwangi Pengguna Instagram Yang Kuliah Di Unisma - Ilfan Ahyar; Muhammad Mansur; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThis study aims to determine the effect of Promotion, Trust and Service Quality on purchasing decisions, the sample of this study are students from Banyuwangi who are studying at UNISMA. For data collection using a questionnaire, to analyze data using validity test, reliability test, normality test, multiple linear analysis, F statistical test and t statistical test, the coefficient of determination test in the IBM Social Sciences Statistics Package (SPSS) Version 16.0.From the results of calculations with SPSS that are promotion variables, trust and service quality simultaneously and significantly influence purchasing decisions. While partially the promotion variables, trust and service quality have a positive and significant influence on purchasing decisions. Keywords: Promotion; Trust; Quality of Service; Buying Decision